A Analysis of Students’ Perception of English Blended Learning by Jones and Sharma during the Pandemic Covid-19 - Diarni, Dian (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
The COVID-19 pandemic caused the learning process to be carried out at home online. However, based on the evaluation result, online learning has various obstacles that cause online learning not to reach the expected goals. Based on this, the government announced a joint decree to accelerate the limited face-to-face learning. So, several schools have started to apply blended learning. Blended learning is a mix of online learning and face-to-face learning. This research is aimed to know the implementation and the student's perception of English blended learning. The researcher used a qualitative approach and descriptive design with 54 students in tenth grade at SMA Mekar Arum Bandung as the participants. The researcher used observation, field notes, questionnaires, and interviews to collect the data. The result of the research shows that the implementation of blended learning is appropriate with the theory by Jones and Sharma and students have a positive perception of blended learning.